The Utilization of Keprok Orange Fruit (Citrus reticulata) Juice in Mozarella Cheese Manufacturing - Wiwit Hartono; Purwadi Purwadi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2012)
The aim of this study was to know the effect of Keprok Orange Fruit (Citrus reticulata) Juice as a direct acidification to yield, meltability, stretchability, protein and moisture content to Mozarella cheese. The result showed that Keprok orange fruit juice gave a highly significant effect (P<0.01) on protein content of Mozzarella cheese. In the otherwise gave a significant effect (P<0.05) on yield, meltability and moisture content of Mozzarella cheese but did not give a significant effect (P>0.05) on stretchability. The conclusion of this research was the Keprok orange fruit juice concentration of 3 % was the best concentration and suggested to use on Mozzarella cheese manufacturing. Key words: Keprok orange fruit (Citrus reticulata), Mozarella cheese manufacturing